Histopathological effects of hypervitaminosis-D and the protective role of fetuin-A in renal, hepatic, and cardiac tissues in a murine model - Maha A. Mohamed; Mohamed Hussein; Shefaa Moustafa; Yalda Rahmani; Tooba Ahmed Durrani; Shiza Ali; Hafsa Ubaid Chhapra; Elshimaa Ali; Mariam Shadan (Scientific Reports)
Abstract Hypervitaminosis D leads to toxic effects, including hypercalcemia, which can cause severe damage to various organs. Fetuin-A, a glycoprotein with anti-inflammatory properties, may protect tissues from such damage. This study explores the role of Fetuin-A in mitigating hypervitaminosis D-induced damage in renal, hepatic, and cardiac tissues. The objectives of this study were to: (1) Assess the extent of tissue damage from high-dose vitamin D in a murine model by examining the histopathological changes in liver, kidney and heart. (2) Investigate Fetuin-A's protective effect against this damage. Thirty-six albino rats were divided into four groups: (1) control, (2) vitamin D toxicity, (3) Fetuin-A + vitamin D, and (4) Fetuin-A only. Vitamin D was administered subcutaneously at 250 μg/20 g/day for 3 days. Fetuin-A was given at 100 μl/20 g, starting 7 days before vitamin D treatment. Histopathological analysis of liver, kidney, and heart tissues was performed using H&E and Alizarin Red staining and findings were analysed statistically. Vitamin D toxicity caused significant tissue damage, including apoptosis, inflammation, and calcification in the liver, kidneys, and heart. Pre-treatment with Fetuin-A reduced calcification and inflammation, preserving tissue architecture. Fetuin-A-only rats showed no damage or calcification. Fetuin-A provided statistically significant protection against vitamin D-induced damage, reducing oxidative stress and calcification in affected organs. These findings suggest Fetuin-A could be a potential therapeutic agent for hypervitaminosis D.